MACEDON RULE IN EGYPT: A GENERAL EVALUATION ON THE PERIOD OF PTOLEMAIOUS - Yılmaz, Cuma Ali (Hamza ALTIN, 2022)
Ptolemy, who was a close friend of Macedonian King Alexander the Great from his youth, became first the king's guard and then one of the generals of the Macedonian army after Alexander the Great ascended the throne. With the sudden death of Alexander the Great in 323 BC, the Macedonian Empire was disintegrated and the Babylonian Council was established by the prominent statesmen of Macedonia to determine who the heir to the throne would be and how the country would be governed. At the end of the council, the imperial lands were divided among Alexander the Great's generals. In this sharing, Ptolemy became the satrap of Egypt. The absolute dominance of the Ptolemaic dynasty in Egypt was finally ensured in 305 BC, after the war between the generals of the Macedonian Empire, called the War of the Diadochi. After Ptolemy I secured his kingdom in Egypt, he organized various expeditions to distant regions such as Cyprus, Syria and Cyrene and took them under control. After gaining absolute dominance in the regions he conquered, his son II. He made Ptolemy a partner in the administration of the country and made him the regent and prepared him for the kingdom. After Ptolemy I became the king of Egypt, he took the title of "Soter", that is, "redeemer". Ptolemy Soter declared himself Pharaoh as well as king. Ptolemy I, who made important socio-cultural contributions to Egypt during his rule, died in 283 BC at the age of 84, and his son II. Ptolemy ascended the throne. Following his father's footsteps in foreign policy, II. In approximately the third year of Ptolemy's reign, the State of Egypt became the naval power of the Eastern Mediterranean. Queen of the Ptolemaic dynasty VII. It continued until Cleopatra. Hellenistic Ptolemaic dynasty in Egypt in 31 BC, Queen VII. It ended with the defeat of the war with the Roman Empire in the period of Cleopatra. From this date on, Egypt became a Roman province. In the introduction part of our study, the annexation of Egypt to Macedonia, the activities of Ptolemy I from Macedonian army general to being king of Egypt and will be discussed. Under subtitles, Ptolemaic I era in, the political, social and cultural situation of Egypt in the said period will be discussed. In the conclusion part of our study, the role of the Ptolemaic dynasty in the spread of Hellenistic culture in Ancient Egypt and its effectiveness in the region will be evaluated.

Makedonya Kralı Büyük İskender’in gençlik yıllarından yakın arkadaşı olan Ptolemaios, Büyük İskender’in tahta çıkmasıyla birlikte, önce kral muhafızı ardından Makedonya ordusunun generallerinden biri olmuştur. Büyük İskender’in MÖ 323 yılında ani ölümüyle birlikte Makedonya İmparatorluğu parçalanmış ve taht varisinin kim olacağı, ülkenin nasıl yönetileceği hususunda Makedonya’nın ileri gelen devlet adamları tarafından Babil Konseyi kurulmuştur. Konseyin sonunda imparatorluk toprakları Büyük İskender’in generalleri arasında paylaşılmıştır. Bu paylaşımda Ptolemaios, Mısır satrapı olmuştur. Ptolemaios hanedanlığının Mısır’daki mutlak hâkimiyeti ise, Diadokhlar Savaşı denilen, Makedonya İmparatorluğu’nun generalleri arasında çıkan savaş nihayetinde, MÖ 305 yılında sağlanmıştır. I. Ptolemaios, Mısır’da krallığını güvence altına aldıktan sonra Kıbrıs, Suriye, Kirene gibi uzak bölgelere çeşitli seferler düzenleyip kontrol altına almıştır. Ele geçirdiği bölgelerde mutlak hâkimiyet sağladıktan sonra oğlu II. Ptolemaios’u ülke yönetimine ortak edip kral naibi yaparak, onu krallığa hazırlamıştır. I. Ptolemaios, Mısır kralı olduktan sonra “Soter” yani “kurtarıcı” unvanını almıştır. Ptolemaios Soter, krallığın yanı sıra kendisini Firavun ilan etmiştir. Hâkimiyeti süresince Mısır’a sosyo-kültürel anlamda önemli katkıları bulunan I. Ptolemaios’ın MÖ 283 yılında 84 yaşındaki ölümün ardından oğlu II. Ptolemaios tahta çıkmıştır. Dış politikada babasının izinden giden, II. Ptolemaios’ın saltanatının yaklaşık olarak üçüncü yılında, Mısır Devleti Doğu Akdeniz’in deniz gücü haline gelmiştir. Ptolemaios hanedanlığı Kraliçe VII. Kleopatra’ya kadar devam etmiştir. Mısır’da Helenistik Ptolemaios hanedanlığı MÖ 31 senesinde, kraliçe VII. Kleopatra döneminde, Roma İmparatorluğu ile yapılan savaştan yenilgiyle çıkılmasıyla son bulmuştur. Bu tarihten itibaren Mısır, Roma eyaleti olmuştur. Çalışmamızın giriş kısmında, Mısır’ın Makedonya topraklarına katılması, I. Ptolemaios’ın Makedonya ordu generalliğinden, Mısır kralı olmasına kadar geçen süreçteki faaliyetlerine değinilecektir. Alt başlıklar halinde I. Ptolemaios dönemi Mısır’ın söz konusu dönemdeki siyasi, sosyal, kültürel durumu ele alınacaktır. Çalışmamızın sonuç kısmında Helenistik kültürün Antik Mısır’da yayılmasında Ptolemaios hanedanlığının rolü ve bölgedeki etkinliği değerlendirilecektir.
MISIR’DA MAKEDON HAKİMİYETİ: I. PTOLEMAIOS DÖNEMİ ÜZERİNE GENEL BİR DEĞERLENDİRME